2014
DOI: 10.1590/1807-3107bor-2014.vol28.0023
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical evaluation of subcrestal dental implants with different bone anchorages

Abstract: This study evaluated the biomechanical influence of apical bone anchorage on a single subcrestal dental implant using three-dimensional finite element analysis (FEA). Four different bone anchorage designs were simulated on a posterior maxillary segment using one implant with platform switching and internal Morse taper connection as follows: 2 mm subcrestal placement with (SW) or without (SO) the implant apex engaged into the cortical bone or position at bone level with anchorage only in the crestal cortical (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 27 publications
1
16
0
2
Order By: Relevance
“…This stability can be influenced by multiple factors, such as the density of the recipient bone, the surgical technique or the design of the implant itself (3). Regarding bone density, several authors have shown that the presence of cortical bone increases the primary stability of the implant, since it provides one or several anchorages in a bone of a much greater density compared to implants fixed only in the trabecular bone, which is much less dense (4)(5)(6)(7)(8)(9)(10). However, it would be appropriate to discuss which of the two cases would produce the best osseointegration or the best biomechanical behaviour in response to the load.…”
Section: Introductionmentioning
confidence: 99%
“…This stability can be influenced by multiple factors, such as the density of the recipient bone, the surgical technique or the design of the implant itself (3). Regarding bone density, several authors have shown that the presence of cortical bone increases the primary stability of the implant, since it provides one or several anchorages in a bone of a much greater density compared to implants fixed only in the trabecular bone, which is much less dense (4)(5)(6)(7)(8)(9)(10). However, it would be appropriate to discuss which of the two cases would produce the best osseointegration or the best biomechanical behaviour in response to the load.…”
Section: Introductionmentioning
confidence: 99%
“…2D). Torque ratchet is used for the final placement and the resistance of the implant is 41 Single-drill under preparation 42,43 Self-drilling active threaded implant for bicortical basal bone engagement 44 Tall implants to engage cortical plates (16-57 mm) [45][46][47] Tilted implants (15-65°) to have more bone implant contact 48,49 Rigid splinting with screw-retained solution for retrievability 50 Platform switching abutment with no micromovement at implant abutment junction 51 Flapless subcrestal placement (pin hole procedure) 52 Immediate prosthesis within 3 days to a week time The primary stability of the implant is, thus, checked with the torque test to determine the loading protocol ( Fig. 2E).…”
Section: Armamentariummentioning
confidence: 99%
“…Apical cortical anchorage can be effective in limiting implant displacement. 63 Thus, bicortical anchorage with subcrestal placement is the advantage which TTPHIL-ALL TILT™ concept provides.…”
Section: Follow Upmentioning
confidence: 99%
“…In the latter technique, teeth with poor bone support are splinted and thus, tooth mobility is minimized. [6][7][8] Different techniques are available for splinting of mobile teeth to their adjacent teeth; 9 these techniques are divided into two groups of extracoronal and intra-coronal techniques. 10 Intra-coronal splints are not often recommended since they require tooth preparation and removal of tooth structure.…”
Section: Introductionmentioning
confidence: 99%